A dynamic history of admixture from Mediterranean and Carpathian glacial refugia drives genomic diversity in the bank vole - Horníková, Michaela; Marková, Silvia; Lanier, Hayley C; Searle, Jeremy B; Kotlík, Petr (Ecology and evolution, 2021)
Understanding the historical contributions of differing glacial refugia is key to evaluating the roles of microevolutionary forces, such as isolation, introgression, and selection in shaping genomic diversity in present-day populations. In Europe, where both Mediterranean and extra-Mediterranean (e.g., Carpathian) refugia of the bank vole (Clethrionomys glareolus) have been identified, mtDNA indicates that extra-Mediterranean refugia were the main source of colonization across the species range, while Mediterranean peninsulas harbor isolated, endemic lineages. Here, we critically evaluate this hypothesis using previously generated genomic data (>6,000 SNPs) for over 800 voles, focusing on genomic contributions to bank voles in central Europe, a key geographic area in considering range-wide colonization. The results provide clear evidence that both extra-Mediterranean (Carpathian) and Mediterranean (Spanish, Calabrian, and Balkan) refugia contributed to the ancestry and genomic diversity of bank vole populations across Europe. Few strong barriers to dispersal and frequent admixture events in central Europe have led to a prominent mid-latitude peak in genomic diversity. Although the genomic contribution of the centrally located Carpathian refugium predominates, populations in different parts of Europe have admixed origins from Mediterranean (28%-47%) and the Carpathian (53%-72%) sources. We suggest that the admixture from Mediterranean refugia may have provisioned adaptive southern alleles to more northern populations, facilitating the end-glacial spread of the admixed populations and contributing to increased bank vole diversity in central Europe. This study adds critical details to the complex end-glacial colonization history of this well-studied organism and underscores the importance of genomic data in phylogeographic interpretation.
Keywords: SNP; admixture; Myodes glareolus; postglacial colonization; genotyping‐by‐sequencing